The Use of Team Word Webbing in Writing Skill for EFL Students - Prasetyaningrum, Ari (Universitas Hamzanwadi, 2018)
The purposes of this study were examining whether the use of team word webbing iis effective in writing skill for the first semester students of Hamzanwadi University in the academic year 2017-2018 and examining how effective was team word webbing in teaching writing for the first semester students of Hamzanwadi university in the academic year 2017-2018. Pre-experimental design was applied for this research since it had experimental group only without control group. The sample of this study was 70 of 120 students. The data was collected through a pre-test and a post-test which were given to the EFL students.To analyze the data, the author applied SPSS 22 for Windows. After submitting the data to paired samples t-test, it was found that there was a significant difference in the mean scores between the pre-test and post-test, which was t (df=18) = 10.550 at p = .000 which lower than 0.05 as the standard significance level in SPSS at two tails. In short, team word webbing technique was significantly effective in writing skillfor the EFL students. Having considered the process and the result of this study, he author suggestedthat English teachers use team word webbing in teaching writing in language learning because it helps student to express their ideas and can become more creative in teaching learning process especially in writing skill.